Effect of spraying with Ferti Mar and GROWX AMINO MIX on some chemical characteristics of Citrus aurantium seedlings Citrus aurantium L. - Mahmoud S. Abdel-Wahed; Mohammed Ghani Mohsen (University of Thi-Qar Journal of agricultural research, 2022)
The experiment was carried out in the Saran-covered nursery of the Department of Horticulture and Landscaping - College of Agriculture and Marshes at Dhi Qar University during the growing season (2021-2022). One-year-old citrus seedlings were obtained as homogeneous in growth as possible from one of the Baghdad governorate nurseries on February 20. \2022 The seedlings were transferred to plastic pots with a capacity of 10 kg (26 cm diameter) filled with an agricultural medium consisting of mixed soil and moss in a ratio of 1:3. The process of servicing the plants was carried out in a similar way, such as pruning, hoeing, fertilizing and irrigation throughout the study period, the study was carried out as a two-factor experiment using the design of sectors Complete Randomization (R.C.B.D)‚ The first factor represented the spraying with Ferti Mar compound at four concentrations (1.5,1,0.5,0) ml per liter-1 and the second factor spraying with the GROWX AMINO MIX compound at four concentrations (0, 1, 2, 3) g per liter-1, and it was sprayed at a rate of three sprays Between one spray and another two weeks, and the results of the study can be summarized as follows: Ferti mar spraying treatments showed a positive effect on most chemical indicators of citrus seedlings. The spraying treatment with a concentration of 1.5 ml L-1 significantly outperformed by registering the highest rate for the character and content of leaves from total chlorophyll, carbohydrates and content of leaves from elements The nutritional value of nitrogen, phosphorous and potassium was 59.89 mg, 100 g-1 fresh weight, 11.260%, 1.83%, 0.24%, and 1.98%, respectively.Spraying treatments with Growx amino mix showed a positive effect on most of the chemical indicators of citrus seedlings. The spraying treatment with a concentration of 3 gm l-1 was superior by recording the highest rate of chlorophyll in leaves, carbohydrate percentage in leaves and leaf content of nutrients nitrogen, phosphorous, potassium, which amounted to 59 .88 mg 100 g-1 mw, 11.361%, 1.80%, 0.24%, 1.89%, respectively.The interaction treatments between the two factors of the study gave a positive significant effect in most of the studied chemical characteristics. The interaction treatment between the concentration of 1.5 ml L-1 of ertimar and 3 gm L-1 Growx amino mix recorded the best significant results for growth indicators.